1999
DOI: 10.1016/s0969-2126(00)88348-3
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli large ribosomal subunit at 7.5 Å resolution

Abstract: Single-particle cryo-EM is rapidly evolving towards the resolution levels required for the direct atomic interpretation of the structure of the ribosome. Structural details such as the minor and major grooves in rRNA double helices and alpha helices of the ribosomal proteins can already be visualised directly in cryo-EM reconstructions of ribosomes frozen in different functional states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 34 publications
(67 reference statements)
2
96
1
2
Order By: Relevance
“…The mismatch regions of the 50S subunit are distributed around its periphery, primarily associated with its proteins. None of the matching RNA regions participate in ligand interactions in the 30S subunit, but many of these helices in the 50S (Pioletti et al 2001;Yusupov et al 2001;Klaholz et al 2003;Rawat et al 2003) and regions found to be flexible in comparative structural studies (see Matadeen et al 1999;Yusupov et al 2001;Ogle et al 2002;Klaholz et al 2003;Rawat et al 2003) mapped into crystal structures of the 30S subunit (PDB identification: 1GIX; Yusupov et al 2001). (D) Secondary structure diagram of the 23S RNA, 5S RNA, and associated proteins, colored in dark gold if data available for the region generally were in good agreement (<25% of mismatch); blue, >25% of mismatches; and gray, no data in our data set.…”
Section: Distribution Of Mismatchesmentioning
confidence: 99%
See 1 more Smart Citation
“…The mismatch regions of the 50S subunit are distributed around its periphery, primarily associated with its proteins. None of the matching RNA regions participate in ligand interactions in the 30S subunit, but many of these helices in the 50S (Pioletti et al 2001;Yusupov et al 2001;Klaholz et al 2003;Rawat et al 2003) and regions found to be flexible in comparative structural studies (see Matadeen et al 1999;Yusupov et al 2001;Ogle et al 2002;Klaholz et al 2003;Rawat et al 2003) mapped into crystal structures of the 30S subunit (PDB identification: 1GIX; Yusupov et al 2001). (D) Secondary structure diagram of the 23S RNA, 5S RNA, and associated proteins, colored in dark gold if data available for the region generally were in good agreement (<25% of mismatch); blue, >25% of mismatches; and gray, no data in our data set.…”
Section: Distribution Of Mismatchesmentioning
confidence: 99%
“…The same color scheme as in D, but rendered in three dimensions. (F) Ligand-binding regions and regions found to be flexible in comparative structural studies (Matadeen et al 1999;Yusupov et al 2001;Klaholz et al 2003;Rawat et al 2003) mapped into crystal structures of the 50S subunit (PDB identification: 1GIY; Yusupov et al 2001). Landmarks show macroscopic features of the 30S and 50S subunits known from electron microscopy: h indicates head; bk, beak; sp, spur; and CP, central protuberance (where the 5S RNA is located); as well as proteins L1, L9, and L7/L12 dimer.…”
Section: Distribution Of Mismatchesmentioning
confidence: 99%
“…Failure to correct the CTF accurately can produce significant mass misplacements in the 3-D reconstruction, such as the exaggeration of holes and protrusions. Various methods for making CTF corrections during the 3-D reconstruction of single particles have been introduced (for instance, Böt-tcher et al, 1997;Trus et al, 1997;Zhu et al, 1997;Conway and Steven, 1999;Ludtke et al, 1999;Matadeen et al, 1999;Zhou et al, 2000). Improper correction of E(s) will lead to either a model in which real features are not resolvable or one in which noisy features are unduly magnified.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Because of advances in experimental and computational techniques, the resolution of single particle reconstructions has reached beyond 9 Å (Böttcher et al, 1997;Conway et al, 1997;Trus et al, 1997;Matadeen et al, 1999;Mancini et al, 2000;Zhou et al, 2000). In order to extend the analysis toward atomic resolution, it will be necessary to include many more particle images containing high-resolution information (Henderson, 1995;Glaeser, 1999;Thuman-Commike et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include studies of various viruses Böttcher et al, 1997b;Conway et al, 1997;Leiman et al, 2004;Morais et al, 2005;Zhou et al, 2000), virus/receptor complexes (Belnap et al, 2000;Bubeck et al, 2005;Hewat et al, 2000;Rossmann et al, 2002;Xiao et al, 2005a), many important cellular complexes such as ribosomes (Allen et al, 2005;Matadeen et al, 1999), nuclear pores (Beck et al, 2004), bacterial flagella (Yonekura et al, 2005), GroEL , membrane Ca 2+ channels (Serysheva et al, 2005), ATPases (Bernal and Stock, 2004;Chen et al, 2004), and many large protein complexes (Acehan et al, 2002;Cheng et al, 2004;Ishikawa et al, 2004;Zhou et al, 2001). Cryo-EM has significantly improved in the last ten years to achieve sub-nanometer resolution, where secondary structural features become visible (Böttcher et al, 1997b;Conway et al, 1997;van Heel et al, 2000;Zhou et al, 2000).…”
Section: Introductionmentioning
confidence: 99%